The Implementation of Gamification to Enhance Grammar and Vocabulary In EFL Students' Writing Skills - Muhammad Rayhan; Usman, Sriati; Patmasari, Andi; Erniwati (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This research objective aims to explore the effects of gamification in improving students' English writing skills. Many students face challenges in developing this skill due to limited vocabulary and difficulties with grammar. The study focused on 10th-grade high school students using a quasi-experimental design with a quantitative approach . Data were collected by using pre-test and post-test assessments of recount text writing. The quality of writing was evaluated using criteria such as content, organization, vocabulary, grammar, and mechanics, based on Heaton's (1988) framework. Findings indicated that the experimental group, which utilized gamification, achieved a better mean score (28.22) compared to the control group (24.64). However, Mann-Whitney test results indicate there is no statistically significant difference between the groups (p = 0.393 > 0.05). This implies that while gamification shows potential in improving grammatical accuracy and vocabulary in writing, its impact remains statistically insignificant. The study suggests that for gamification to be more effective in writing instruction, it may require a longer implementation period, better calibration of task difficulty, and an enhanced feedback system targeting grammar and vocabulary development.